2013
DOI: 10.1371/journal.pone.0068758
|View full text |Cite
|
Sign up to set email alerts
|

A Cleavable N-Terminal Signal Peptide Promotes Widespread Olfactory Receptor Surface Expression in HEK293T Cells

Abstract: Olfactory receptors (ORs) are G protein-coupled receptors that detect odorants in the olfactory epithelium, and comprise the largest gene family in the genome. Identification of OR ligands typically requires OR surface expression in heterologous cells; however, ORs rarely traffic to the cell surface when exogenously expressed. Therefore, most ORs are orphan receptors with no known ligands. To date, studies have utilized non-cleavable rhodopsin (Rho) tags and/or chaperones (i.e. Receptor Transporting Protein, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 42 publications
4
96
0
Order By: Relevance
“…1d, Flag-tagged full-length constructs encoding OR1J1, OR6A2 and OR51E2 were able to traffic to the cell surface under certain conditions; surface expression of OR51E2 was the most pronounced among the three ORs. In fact, OR51E2 incorporated into the plasma membrane without the aid of an N-terminal leucine-rich cleavable signal peptide (Lucy tag, as previously described34), or co-expression of RTP1S and Ric8b chaperones (Fig. 1d).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1d, Flag-tagged full-length constructs encoding OR1J1, OR6A2 and OR51E2 were able to traffic to the cell surface under certain conditions; surface expression of OR51E2 was the most pronounced among the three ORs. In fact, OR51E2 incorporated into the plasma membrane without the aid of an N-terminal leucine-rich cleavable signal peptide (Lucy tag, as previously described34), or co-expression of RTP1S and Ric8b chaperones (Fig. 1d).…”
Section: Resultsmentioning
confidence: 97%
“…ORs identified in ASM by degenerate primer PCR were cloned into the PME18S mammalian expression vector containing N terminal Lucy, Flag and Rho tags as previously described34. These constructs were then transfected into HEK 293T cells with and without the chaperone proteins RTP1S and Ric8b.…”
Section: Methodsmentioning
confidence: 99%
“…Olfr78 in the afferent arteriole [64]), these receptors clearly must be signaling through a different G protein. Consistent with this, ORs in vitro can also couple to G s (or, under specific conditions, G q ) [31; 32; 39; 60; 64; 65]. In addition, a handful of ORs have been found to be expressed in the vomeronasal organ, the site of pheromone sensing in the mouse, where they are also thought to couple to other G proteins [66; 67].…”
Section: Characterizing or Signaling In The Kidneymentioning
confidence: 88%
“…A second possible approach to screening ORs is to use a variety of aids to help the OR achieve surface expression when exogenously expressed in vitro . A number of studies have identified either chaperones or N-terminal tags which aid in OR surface expression [3953], and when successful this allows for a high-throughput approach focused on a specific OR.…”
Section: Special Considerations and Challenges Of Studying Orsmentioning
confidence: 99%
See 1 more Smart Citation